Designing gamification-based worksheets to enhance student learning outcomes in abstract algebra course - Agustyaningrum, Nina; Pradanti, Paskalia (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Many studies report that abstract algebra is a subject students find difficult to understand, although it is a core course in the mathematics education curriculum. This research was motivated by lecturers’ challenges in developing innovative teaching materials that engage students and improve conceptual understanding. The aim was to develop gamification-based student worksheets (LKM) that are valid, practical, and effective in supporting learning outcomes. The research employed the 4D development model by Thiagarajan, which consists of the define, design, development, and dissemination stages. The participants were mathematics education students at Universitas Tidar enrolled in the ring theory course. Research instruments included validation sheets to assess the validity of the materials, student response questionnaires to evaluate practicality, and learning outcome tests on ring theory to assess effectiveness. The results showed that the developed of LKM achieved very high validity (92%), practicality (80%), and effectiveness based on the Wilcoxon test. Therefore, the developed materials are considered appropriate to enhance the learning of abstract algebra in a more interactive and enjoyable manner. The researchers recommend that lecturers of the ring theory course use this LKM as an alternative teaching material to improve students’ understanding of abstract concepts in a more engaging and meaningful way.